Triplet superconducting proximity effect in nonhomogeneous magnetic materials: Статьи, посвященные столетию со дня рождения Л. В. Шубникова - Kadigrobov, A.; Shekhter, R. I.; Jonson, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
We show that quantum spin fluctuations in inhomogeneous conducting ferromagnets drastically affect the Andreev reflection of electrons and holes at a ferromagnet-superconductor interface. As a result, a strong long-range proximity effect appears, associated with electron-hole spin triplet correlationsand persisting on a length scale typical for nonmagnetic materials but anomalously large forferromagnets. For applications, an important consequence is that this long-range proximity effectpermits to create superconducting quantum intetference devices with the Josephson magnetic junction ofan anomalous large length.